Multiplex Detection of Five Canine Viral Pathogens for Dogs as Laboratory Animals by the Luminex xTAG Assay - Wu, Miaoli; Cong, Feng; Zhu, Yujun; Lian, Yuexiao; Chen, Meili; Huang, Ren; Guo, Pengju (Frontiers in Microbiology, 2018)
More and more dogs have been used as a disease model for medical research and drug safety evaluation. Therefore, it is important to make sure that the dogs and their living houses are special pathogen free. In this study, the development and evaluation of a Luminex xTAG assay for simultaneous detection of five canine viruses was carried out, including canine distemper virus, canine parvovirus, canine parainfluenza virus, canine adenovirus and rabies virus. Assay specificity was accomplished by targeting conserved genomic regions for each virus. Hybridization between multiplexed PCR products and the labeled fluorescence microspheres was detected in a high throughput format using a Luminex fluorescence reader. The Luminex xTAG assay showed high sensitivity with limits of detection for the five viruses was 100copies/μL. Specificity of the xTAG assay showed no amplification of canine coronavirus, pseudorabies virus and canine influenza virus indicating that the xTAG assay was specific. 75 clinical samples was tested to evaluate the xTAG assay. The results showed 100% coincidence with the conventional PCR method. This is the first report of a specific and sensitive multiplex Luminex xTAG assay for simultaneous detection of five major canine viral pathogens. This assay will be a useful tool for quality control and environmental monitoring for dogs used as laboratory animals, may even be applied in laboratory epidemiological investigations.